Metods of diagnostic in the head-brain injury. - V. V. Kosharniy; A. I. Pavlov; S. V. Kozlov (Морфологія, 2016)
Background. Injuries are 3rd in the structure of the population mortality. Over the past 15 years, mortality from injury came on second place, ahead of cancer. Traumatic brain injury is the most common damage types and ranges from 36 to 40 % of all injuries. The incidence of posterior fossa hematomas among intracranial hematomas has been reported to be 2 to 3%. Objective. The aim of the present study was to investigate the features of posterior fossa hematoma, including posterior fossa epidural hematoma, posterior fossa subdural hematoma and intracerebellar hematoma. The aim of the study was to determine the clinical features and diagnosis of severe head injuries. Methods. Analyzed the medical records of patients admitted to the Department of Neurosurgery Regional Hospital. They can be: furrow branches of the middle meningeal artery; wedge-parietal sulcus sinus; Channels diploic veins; cleft wedge - occipital synchondrosis behind the backs of the pituitary fossa; occipital-mastoid suture. Results and conclusion. With the introduction of the practice of computer and magnetic resonance imaging to diagnose damage to structures in the presence of hematomas in the posterior fossa it became much easier. Since patients are not always in a conscious state data instrumental methods of diagnosis in a very short time allow the diagnosis and differential diagnosis in injuries that are accompanied by the presence of intracranial hematomas in the posterior fossa.